2008
DOI: 10.1002/nau.20575
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic detrusor overactivity: Comparison between complete and incomplete spinal cord injury patients

Abstract: No difference in cystometric capacity and intravesical leak point pressure at terminal detrusor overactivity was shown between complete and incomplete spinal cord injury patients in our survey, that is, represented findings are equally unfavorable for both groups. Incomplete SCI patients with NDO should be tested with cystometry and observed with same caution as we proceed in complete SCI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…DO is a common consequence of suprasacral spinal cord injury along with loss of motor and sensory functions below the injury level. 15 The significant difference observed in urine emptying disorder frequency and storage disorder frequency between the ischemic and hemorrhagic stroke groups in this study is intriguing. It seems, however, confusing to describe the observed significant difference in the frequencies of urine emptying and storage disorder between the hemorrhagic and ischemic stroke groups, but some possible assumptions are as follows:…”
Section: Discussionmentioning
confidence: 69%
“…DO is a common consequence of suprasacral spinal cord injury along with loss of motor and sensory functions below the injury level. 15 The significant difference observed in urine emptying disorder frequency and storage disorder frequency between the ischemic and hemorrhagic stroke groups in this study is intriguing. It seems, however, confusing to describe the observed significant difference in the frequencies of urine emptying and storage disorder between the hemorrhagic and ischemic stroke groups, but some possible assumptions are as follows:…”
Section: Discussionmentioning
confidence: 69%
“…Studies investigating lesion severity and bladder function found no significant difference between complete and incomplete lesions in terms of maximum detrusor pressure and MC (21); mean MC and mean intravesical leak-point pressures were not significantly different between AIS-A and AIS B-E patients (22); although DO was more benign in AIS-B patients than in AIS-A patients, neuropathic bladder type and compliance were not significantly different between AIS-A and AIS-B patients (23). Scivoletto et al (24) have shown that none of the patients with AIS-A impairment on admission reached volitional voiding at 5 months; AIS-B patients had a 90% lower probability of achieving good bladder control and AIS-C patients had 65% lower than AIS-D patients.…”
Section: Discussionmentioning
confidence: 82%
“…However, previous investigators have noted an inexact correlation between somatic neurological findings and characteristic urodynamic findings. 1,[3][4][5]16,17 It was shown with urodynamic evaluation that lower urinary system dysfunction may be present in patients who are neurologically intact in a study conducted on 44 patients with SCI with a thoracolumbar level lesion. 18 Another study on 64 patients with chronic SCI in an ambulatory state reported that a deterioration of bladder functions can be present with AIS D and AIS E and that detrusor hyperactivity is also important for ambulatory patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, it has been reported that somatic neurological findings are not always consistent with urodynamic findings. [3][4][5] The disorder may be overlooked, particularly in patients with incomplete injury. Clinicians may not be aware of the seriousness of urinary tract dysfunction in patients with incomplete injury, especially in those that are ambulatory, and lifethreatening complications such as recurrent urinary tract infection, vesicoureteral reflux (VUR), hydronephrosis and renal failure may develop.…”
Section: Introductionmentioning
confidence: 99%